2005
DOI: 10.1128/aem.71.1.261-269.2005
|View full text |Cite
|
Sign up to set email alerts
|

A clp Gene Homologue Belonging to the Crp Gene Family Globally Regulates Lytic Enzyme Production, Antimicrobial Activity, and Biological Control Activity Expressed by Lysobacter enzymogenes Strain C3

Abstract: Lysobacter enzymogenes strain C3, a biological control agent for plant diseases, produces multiple extracellular hydrolytic enzymes and displays antimicrobial activity against various fungal and oomycetous species. However, little is known about the regulation of these enzymes or their roles in antimicrobial activity and biocontrol. A study was undertaken to identify mutants of strain C3 affected in extracellular enzyme production and to evaluate their biocontrol efficacy. A single mini-Tn5-lacZ 1 -cat transpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
95
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(98 citation statements)
references
References 43 publications
3
95
0
Order By: Relevance
“…These results indicated that the production of extracellular chitinase and antifungal activity in L. enzymogenes C-3 were not directly correlated. Previous work in L. enzymogenes C3 showed that reduction of production of extracellular chitianse, protease, and antimicrobial activity (Kobayashi et al, 2005). In this study, mutant 17 (Clp) showed similar phenotypes as the Clp mutant of C3.…”
supporting
confidence: 62%
See 2 more Smart Citations
“…These results indicated that the production of extracellular chitinase and antifungal activity in L. enzymogenes C-3 were not directly correlated. Previous work in L. enzymogenes C3 showed that reduction of production of extracellular chitianse, protease, and antimicrobial activity (Kobayashi et al, 2005). In this study, mutant 17 (Clp) showed similar phenotypes as the Clp mutant of C3.…”
supporting
confidence: 62%
“…In previous work of other group, a similar approach was used to identify a global regulator of chitinase production, and the Clp protease was identified as a global regulator of expression of extracellular chitinase and biocontrol traits in L. enzymogenes (Kobayashi et al, 2005). Interestingly, a transposon inserted in the speD gene, which is located to juxtaposition of the clp gene in the mutant M10, showed similar phenotypes in the production of extracellular lytic enzyme.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…And in pseudomonads as well as other bacteria, other global regulators are likely to be present and relevant. For example, a clp gene homolog has been shown to be an important regulator of multiple biocontrol phenotypes in Lysobacter enzymogenes (30).…”
Section: Regulation Of Secondary Metabolism and Biocontrolmentioning
confidence: 99%
“…Involvement of transcription factors in the regulation of expression of lytic enzymes was shown for L. enzymogenes strain C3. In this strain, the production of lytic enzymes is regulated by the product of the gene clp, which has been assigned to the CRP family of global transcription regulators (23). Thus, on the basis of the results of the analysis of the nucleotide sequences and cellular transcripts of alpA and alpB, it can be concluded that these genes are each transcribed from their own promoters.…”
Section: Resultsmentioning
confidence: 99%